Precision Functional Mapping of Corticostriatal and Corticothalamic Circuits: Parallel Processing Reconsidered - Lynch, Charles J.; Liston, Conor (Neuron (Cambridge, Mass.), 2020)
In this issue of Neuron, Greene et al. (2020) identify zones of network specificity and multi-network integration in the basal ganglia and thalamus of individual human subjects. Such information could aid in the development of personalized and more effective brain stimulation therapies for neuropsychiatric disorders. In this issue of Neuron, Greene et al. (2020) identify zones of network specificity and multi-network integration in the basal ganglia and thalamus of individual human subjects. Such information could aid in the development of personalized and more effective brain stimulation therapies for neuropsychiatric disorders.